Manajemen Komunikasi Dakwah Pemberdayaan Masyarakat melalui Lazisnu Kota Padangsidimpuan - Juni Wati Sri Rizki; Esli Zuraidah Siregar (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
This study aims to determine the urgency of community Manajement in community empowerment in Tabagsel. Both community empowerment in the fields 0f socio cultural, economic, edukasi and health. The form of research is field reseach with a descriptive qualitative approach combined with phenemonogi. The theory used is the communication manajement theory from Nobel & Herbert Simon and the empowerment corcept from Robert Chambers. The results showed that the communication management applied by Lazisnu Tabagsel was not optimal. POAC as an element of communication management has not been implemented. Community empowerment through the NU Coins movement is carried out through the zero rupiah balance system. The Allocation is done every two weeks by spending the entire balance obtained collecting NU Coins. Lazisnu’s work program seeks to improve the walfare of the communicy in the socio-religius, economic, education and health fields. The impact of this research is expected to provide scientific contributions in improving the walfare of the community.